2008
DOI: 10.1093/ajcn/88.4.950
|View full text |Cite
|
Sign up to set email alerts
|

Positive energy balance is associated with accelerated muscle atrophy and increased erythrocyte glutathione turnover during 5 wk of bed rest

Abstract: Positive energy balance during inactivity is associated with greater muscle atrophy and with activation of systemic inflammation and of antioxidant defenses. Optimizing caloric intake may be a useful strategy for mitigating muscle loss during period of chronic inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 32 publications
5
114
0
1
Order By: Relevance
“…Progressive reduction of physical activity is further observed with disease progression due to worsening obesity and its joint and musculoskeletal complications [22], with direct negative impact on muscle protein turnover and muscle oxidative and performance capacity [39,40]. …”
Section: Introduction: What We Knowmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive reduction of physical activity is further observed with disease progression due to worsening obesity and its joint and musculoskeletal complications [22], with direct negative impact on muscle protein turnover and muscle oxidative and performance capacity [39,40]. …”
Section: Introduction: What We Knowmentioning
confidence: 99%
“…The latter include muscle fat accumulation that reduces muscle density and quality with lower contractile protein content per unit tissue [35,53,54], mitochondrial dysfunction that may cause impaired ATP production, and maximal oxygen consumption leading to both reduced strength and endurance [21]. Physical inactivity that reduces muscle mass, mitochondrial biogenesis and function, and tissue lipid oxidation, also leads to reduced strength and endurance potentially enhancing tissue and systemic inflammation and oxidative stress [39,40,55]. …”
Section: Introduction: What We Knowmentioning
confidence: 99%
“…Further the concept of counting only non-protein calories, but not including the energy from proteins, contributed to overfeeding. Th is way to calculate energy intake should defi nitively be banned: All energy sources should be included in the total energy counts [23,24]. Finally, a computerized information system is needed to be aware of the rather important amounts of energy infused for non-nutritional purpose, including glucose 5% solutions and fat soluble sedatives [25].…”
Section: Consequences Of Under-and Over-feedingmentioning
confidence: 99%
“…Th e problem is that all patients were overfed, the pseudo-lowcalorie group being less overfed than the other, so of course doing better! As previously stated, all substrates must be included in the calculations [24]! After a study by Fong et al in volunteers given endotoxin [27], parenteral nutrition became considered a poison, because its delivery had primed a stronger infl ammatory response compared with enteral nutrition.…”
Section: Underfeeding and Pseudo-underfeedingmentioning
confidence: 99%
“…However, the determination of nutritional requirements in critical illness remains controversial. There is some limited data from the bed rest (aerospace) literature suggesting that overfeeding may be harmful, with increased inflammatory markers and accelerated muscle atrophy in participants who do not reduce caloric intake after the initiation of bed rest (Biolo et al, 2008). Congruent with this, a recent study in critical illness found that permissive underfeeding (goal 60-70% of estimated nutritional requirements) resulted in lower hospital mortality compared to those fed with a goal of 100% of estimated requirements (Arabi et al, 2011).…”
Section: Nutritionmentioning
confidence: 99%